NILAI ISLAM DALAM ADAT MAANTAR JUJURAN PADA PERNIKAHAN SUKU BANJAR DI DESA JONGKAT - Risma Shayrani; Abu Bakar; Nanda Himmatul Ulya (Al-Usroh, 2025)
This research aims to analyze the Maantar Jujuran customary practice within the marriage traditions of the Banjar ethnic group in Jongkat Village, Mempawah Regency, while exploring the inherent Islamic values. This phenomenon is significant as it integrates Sharia requirements with local wisdom, which, although often perceived as a materialistic burden, possesses profound philosophical roots. Utilizing a descriptive qualitative method with a field research approach, data were collected through participatory observation and in-depth interviews with customary leaders, religious figures, and cultural practitioners. Data analysis was conducted through the lenses of 'Urf and Value theories to observe the harmonization between Islamic law and local culture. The results demonstrate that Maantar Jujuran in Jongkat Village is not merely an economic transaction, but a manifestation of responsibility (mas'uliyyah), respect (ihtiram), sincerity (ikhlas), and the strengthening of kinship ties (silaturahmi). Juridically and normatively, this tradition is categorized as 'Urf Shahih (sound custom) as it does not contradict the fundamental principles of Sharia; rather, it serves as an instrument for protecting women's rights within a cultural framework.